LANGUAGE LEARNING AND CHARACTER-BUILDING: THE EXPERIENCE OF TEACHING INDONESIAN IN AUSTRALIA - David Reeve (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
To learn a foreign language is to learn that there are other ways of using language than those that we are used to. This can be a shock for people learning a second language for the first time. This teaches students that there are other ways of organising a language and other ways of constructing meaning than those that they were brought up with. As well as providing knowledge about the new language, it teaches learners to see their own first language in a new light. This provides a greater maturity about the state of the world, and about one’s own first language. Whatever the method of language education, this should always apply.